Applying the natural disasters vulnerability evaluation model to the March 2011 north-east Japan earthquake and tsunami - Ruiz Estrada, Mario Arturo; Yap, Su Fei; Park, Donghyun (Disasters, 2014)
Natural hazards have a potentially large impact on economic growth, but measuring their economic impact is subject to a great deal of uncertainty. The central objective of this paper is to demonstrate a model—the natural disasters vulnerability evaluation (NDVE) model—that can be used to evaluate the impact of natural hazards on gross national product growth. The model is based on five basic indicators—natural hazards growth rates (αi), the national natural hazards vulnerability rate (ΩT), the natural disaster devastation magnitude rate (Π), the economic desgrowth rate (i.e. shrinkage of the economy) (δ), and the NHV surface. In addition, we apply the NDVE model to the north‐east Japan earthquake and tsunami of March 2011 to evaluate its impact on the Japanese economy.